PENGARUH PEMBERIAN MINYAK BUAH MERAH (Pandanus conoideus) TERHADAP STRES OKSIDATIF SEL ENDOTEL YANG DIPAPAR DENGAN SERUM PENDERITA MALARIA FALCIPARUM DAN NETROFIL INDIVIDU SEHAT - Armiyanti, Yunita; Fitri, Loeki Enggar; Widjajanto, Edi (Jurnal Kedokteran Brawijaya, 2007)
Complication in Plasmodium falciparum malaria is associated with endothelial damage and overproductionof free radicals (oxidative stress) by activated neutrophils and endothelial cells. Red fruit (Pandanus conoideus) oil  has a very high antioxidant content, therefore it may neutralize free radicals and prevent endothelial damage. The aim of this research is to prove that red fruit (Pandanus conoideus) oil reduce Reactive Oxygen Intermediate (ROI) production  of endothelial cells exposed to severe malaria patient serum and neutrophils from healthy donor. Endothelial cells from human umbilical veins were coincubated with serum from severe malaria patient and with neutrophils from healthy donor  (positive control group). HUVEC’s normal was used as negative control,  where as  the experimental groups were given with red fruit oil in different concentrations (2.8%, 5.7% dan 11.3% ). The Reactive Oxygen Intermediate (ROI) production of  endothelial cells was semiquantitatively measured by using NBT-reduction assay and the score of ROI was counted. The results were statistically analyzed with ANNOVA (p<0.01). The rate of ROI production of endothelial cells was markedly increased after incubation with patient serum and neutrophils.